EFFECT OF BIOFERTILIZER AND ROCK PHOSPHATE ON IRON AVAILABILITY IN SOIL AND THE IRON CONTENT OF LENTIL - Mowafaq Younis Sultan (Mesopotamia Journal of Agriculture)
Field experiment was conducted in Calciorthid to study the effect of biofertilizer( R. Leguminosarum mixture of the three rhizobial strains Le719, Le726 and Le735) and phosphate fertilizers as rock phosphate to determine the content of Iron in the Lentil (Lens culinaris) and its availability in the soil. The experiment was conducted by using (RCBD) this study involved three levels of phosphorus (0, 40, and 80 kg P/H) as rock phosphate besides two levels of inoculation (inoculated with rhizobial bacteria and non inoculated). K was added to all treatments at a rate of 10 kg K/H with three replicates. Samples of soil and plant were taken at three interval times 75, 105, and 137days after seeding for determining iron. Results showed an ability of strains under-study to increase the availability of Iron in the soil and the Lentil content of iron al so application of rock phosphate increase iron in the soil and plant. This study indicated the ability of using the rock phosphate instead of P fertilizer.